URGENSI PENDIDIKAN AL-QUR’AN BAGI MAHASISWA: Permasalahan Tahsin Al-Qur’an Di Perguruan Tinggi dan Solusinya - Mujiburrahman, Mujiburrahman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The Quran is the revered scripture of Muslims, and we continually find inspiration in reciting it. Understanding and practicing its contents is an obligation for Muslims. Before understanding the Quran, one must first be able to read it. Students are expected to be role models in Quranic recitation skills. Muslim students have an individual obligation to be proficient readers of the Quran. They are committing a sin if they continue to read in accordance with their preferences, misinterpret the Quran, or neglect the studies of the Quran. In reality, despite having completed several educational stages, a large number of pupils are unable to correctly recite the Quran. This study aimed to identify the variables affecting students' failure to read the Quran in accordance with Tajweed and to propose solutions. This study used a literature study method, conducted by reviewing several journals and books related to the problem of inability to read the Quran, especially among students. It can be concluded that teaching the Quran to students is very important, because being a student does not guarantee the ability to read the Quran well and correctly. Both internal and external factors may contribute to the pupils' incapacity to read the Qur'an. Internal factors include a lack of motivation and religious awareness, weak mastery of the Hijaiyah letters, and the habit of reading without guidance. The external factors include the teachers (as professionals), the curriculum, the unavailability of competent teachers, an unsupportive environment, the lack of structured learning methods, and psychological and spiritual factors. The two solutions to this issue are 1) encouraging students to have a strong desire to study the Qur'an and 2) acclimating pupils to reciting the Qur'an both alone and in groups.